Communication and Collective Actions: A Survey Experiment on Motivating Energy Conservation in the U.S. Issue 1 (20th August 2014) - Bolsen, Toby; Druckman, James N.; Cook, Fay Lomax
Abstract When do citizens take action to benefit the public good, even when individual benefits are scant or non-existent? We address this question with a focus on an area of critical importance when it comes to environmental sustainability—specifically, we examine citizens' actions in the domain of energy conservation. We do so by using a survey experiment to evaluate the impact of exposure to communications posited to shape collective action behavior. We find that communications shape behavior depending on two primary factors not previously studied in concert: to whom responsibility is attributed for collective outcomes; and, what effects, or consequences, are associated with one's actions. We find that communications emphasizing individual responsibility and collective environmental benefits can stimulate collective action.